A Comparison of Needle Aspiration Versus Incision & Drainage of Breast Abscess in Terms of Complications and Outcomes - Mahour, Kusum; Jain, Siddharth; Garg, Akash; Jhawar, Riddhi; Shree, Mannu (Journal of Neonatal Surgery, 2025)
Background: Incision and drainage (I&D) and Needle aspiration are the most common treatment modalities for breast abscesses. Incision and drainage (I&D) is the traditional approach, while ultrasound-guided needle aspiration (USGA) offers a less invasive alternative. This study aimed to compare the efficacy and outcomes of USGA and I&D in managing breast abscesses in women Methods: This comparative study was carried out in the department of surgery, Sanjay Gandhi Memorial Hospital, Shyam Shah Medical College, Rewa (M.P.). The study included 100 women with breast abscesses, divided into two groups; USG guided aspiration (group A) and I & D (group B). Data on treatment outcomes, and complications were compared and analysed. Results: USG observation shows that the diameter, number and volume of abscess cavity were significantly differ among I & D and aspiration groups (p<0.05). The wound healing were significantly faster (97.7%) among aspiration group as compared to I & D (82.5%) groups (p<0.05). Hypertrophic scar was significantly higher in I & D group (P<0.05) and recurrence rate was higher in aspiration group. Pain score and mean hospital stay was higher in I &D group. Conclusions: Percutaneous needle aspiration in breast abscess was successful and affective treatment method as compared to incision drainage with less complications and high satisfaction rate among the women.